Evaluation of the effectiveness of orthodontic treatment with clear aligners in different wear time protocols: randomized clinical trial - Fialho, Tiago (2025)
Introduction: With the increasing use of clear aligners by orthodontists, some guidelines for use are determined by manufacturing companies without necessarily having studies that support these determinations. The amount of daily hours required to use the aligners is one of these issues, and the type of composite used for the attachments is another. Objective: Evaluate the efficiency of orthodontic aligners performed with different daily protocols and compare the resistance of two fluid resins, conventional and high-load fluids, in manufacturing attachments. Material and Methods: To evaluate the daily wear time of the aligners, 25 participants (9 men, 16 women) with an average age of 38.56 years (± 7.57) used the 22-hour daily protocol, and 25 participants (12 men, 13 women ) with a mean age of 37.15 years (± 6.23) used the 12-hour daily protocol. For the assessment of attachments, the 50 patients (21 men, 29 women) with a mean age of 37.86 years (± 6.90) were divided into a splitmouth design where each participant\'s right and left sides were directly compared for intra-individual assessment. Intergroup comparisons were performed using the t-test (P<0.05). Results: For the evaluation of the time of daily use of the aligners, there was no statistically significant difference in the Little index, intercanine, interpremolar, intermolar distances, Overjet, and Overbite, except for the Little index in the mandible. Regarding the type of resin used in the attachments, there was no statistically significant difference between the use of flowable composites and flowable bulk-fill composites. Conclusion: The 12-hour protocol proved efficient in orthodontic treatment with aligners, except in anterior mandibular crowding, where the 22-hour protocol showed a statistically better result.